Altar of Our Lady of the Rosary Church - Mumbai Archive Project Team (Jio Institute, 2024)
The panel above the altar at Our Lady of the Rosary church features a copy of Leonardo da Vinci's ‘The Last Supper’ mural, which was created between 1495 and 1498 and is housed in the refectory of the Convent of Santa Maria delle Grazie in Milan, Italy. The painting depicts the scene of the Last Supper of Jesus with the Twelve Apostles, as recounted in the Gospel of John.